Immobilized Ag-nanoparticles (iNPs) for environmental applications: Elucidation of immobilized silver-induced inhibition mechanism of Escherichia coli - Theofilou, Stathis P.; Antoniou, Chrystalla; Potamiti, Louiza; Hadjisavvas, Andreas; Panayiotidis, Mihalis I.; Savva, Petros G.; Costa, Costas; Fotopoulos, Vasileios (My University, 2021)
Although silver nanoparticles (AgNPs) appear to be promising for certain medical/pharmaceutical applications, they present significant disadvantages when it comes to environmental applications due to the need for recovery of the metal (Ag) which is considered hazardous for the environment. The present study examines the antimicrobial properties and mechanism of action of immobilized (on Al2O3) silver nanoparticles’ (1 wt% Ag-iNPs) regarding the treatment of E. coli microbial solutions. Antimicrobial experiments were conducted in semi-batch mode using a three-phase continuous flow stirred tank reactor. Every treated sample was taken from the outlet of the reactor for the time intervals of 0, 5 and 25 min. To ensure that the bactericidal property of Ag-iNPs is not attributed to the dissolution of surface silver (as free Ag+), a suitable Ag+ scavenger was used as already described in our earlier studies. Regarding the molecular analysis performed under this study, the regulation of key enzymes involved in bactericidal activity of E. coli, was examined, after their treatment either with immobilized silver nanoparticles (Ag-iNPs) or AgNO3. Specifically, 50 mL sample for each case was centrifuged (10 min at 10,000 rpm) and the pellet (≈109 cells) was immediately subjected to total RNA extraction. For real-time RT-qPCR analyses, 1 μg of total RNA was converted into cDNA. It was found that PldA gene, which encodes outer membrane's phospholipase A (OMPLA), was up-regulated after 5 and 25 min of treatment with Ag-iNPs. OMPLA's activation appears to be the initial step of Ag-iNPs bactericidal mechanism that ultimately leads to the creation of holes on the outer membrane (OM), irreversibly disturbing the cells’ respiration cycle. In addition, after treatment with Ag-iNPs, Blue copper oxidase CueO (encoded by cueO gene) was found to be over-produced and appears to play a key-role in the oxidative transfer of silver from the surface of Ag-iNPs to the cell. This leads to the Ag-induced displacement of copper from its native protein sites such as CusS/CusR, a fact that causes the release of labile copper and ROS inside the cell. In addition, TEM analysis of bacteria treated with Ag-iNPs revealed severe morphological changes (“holes”) on bacterial outer membrane, indicating that there is an intermediate step in the proposed antimicrobial mechanism which takes place on the surface of Ag-iNPs.
Keywords: Ag-iNPs; Antimicrobial mechanism; Genes regulation; Pseudo-catalysis; Silver nanoparticles; Silver toxicity; TEM analysis